Potential Therapeutic Properties of Olea europaea Leaves from Selected Cultivars Based on Their Mineral and Organic Profiles - Natália M. de Oliveira; Jorge Machado; Maria Helena Chéu; Lara Lopes; M. Fátima Barroso; Aurora Silva; Sara Sousa; Valentina F. Domingues; Clara Grosso (MDPI AG, 2024)
Olive leaves are consumed as an extract or as a whole herbal powder with several potential therapeutic benefits attributed to polyphenols, tocopherol's isomers, and flavonoids, among others. This study assessed the potential variance in the functional features presented by olive leaves from three different Portuguese cultivars-Cobrançosa, Madural, and Verdeal-randomly mix-cultivated in the geographical area of Vale de Salgueiros. Inorganic analysis determined their mineral profiles while an organic analysis measured their total phenolic and flavonoid content, and scanned their phenolic and tocopherol and fatty acid composition. The extracts' biological activity was tested by determining their antimicrobial and antioxidant power as well as their ability to inhibit acetylcholinesterase, butyrylcholinesterase, MAO-A/B, and angiotensin-I-converting enzyme. The inorganic profiles showed them to be an inexpensive source able to address different mineral deficiencies. All cultivars appear to have potential for use as possible antioxidants and future alternative antibiotics against some multidrug-resistant microorganisms, with caution regarding the arsenic content in the Verdeal cultivar. Madural's extract displayed properties to be considered a natural multitarget treatment for Alzheimer's and Parkinson's diseases, depression, and cardiometabolic and dual activity for blood pressure modulation. This work indicates that randomly cultivating different cultivars significantly modifies the leaves' composition while keeping their multifaceted therapeutic value.